Determination of Immunity Status of Vaccinated Health Care Workers against Hepatitis B Virus in Khartoum State, Sudan - Mosab Nouraldein Mohammed Hamad (Middle East Research Journal of Medical Sciences, 2024)
Background: The vaccination of health care workers (HCWs) for the hepatitis B virus (HBV) is a crucial part of hospital infection control programs. They are considered to be a population at high risk of developing HBV infection due to the high transmissibility of the virus and the risk related to occupational injuries. The risk is particularly high in HCWs with greater exposure to accidental inoculation at work and is related to the duration of professional activity, the characteristics of the healthcare center, and the type of population served. Objectives: The current study was conducted to evaluate the immunity status of the vaccinated HCWs against HBV in Khartoum State. Materials and Methods: This cross-sectional descriptive laboratory-based study was conducted from December 2022 to February 2023. Data were collected through a structured questionnaire regarding age, gender, type of employment, length of employment, and duration of vaccination for each participant. 90 vaccinated HCWs were enrolled in this study; serum samples were collected from each participant; the Enzyme Linked Immuno Sorbent Assay technique was used to detect the anti-HBs level; and the collected data were analyzed using Statistical Package for the Social Sciences (SPSS). Results: This study included 90 healthcare workers, female 70 (77.8%), male 20 (22.2%) ages ranging from 20 to 52 years old, 45 (50%) of them laboratory specialists, and 23 (23.3%). Nursing 17 (18.9%), Dentists 5 (5.6%), and 2.5 (2.2%). The results of the current study reveal that 70% of the studied vaccinated HCWs have a protective level of HBs-Ab. Of these, 23.3% had an anti-HBs titer between 10 and 100 mIU/ml, and the rest, 46.7%, had an anti-HBs titer >100 mIU/ml, while 30% of them were not protective, 22.2% of them were males, and the rest, 77.8%, were females, with a mean age of 30 years. Conclusion: Though many HCWs had been exposed to the virus before or had received vaccinations, the majority of them were seroprotected against the hepatitis B virus. HCWs must be made aware of the prescribed immunization schedule and must be required to receive all recommended vaccinations.